Echoes at dawn eaudiobook Kgi series, book 5. - Banks, Maya (KGI, 2012)
New York Times best-selling author Maya Banks has built a wide following for her novels featuring the elite Kelly brothers. This fifth KGI novel begins as Grace Peterson escapes a shadowy cabal hellbent on exploiting her mysterious ability to heal others. Enter Rio, the relentless KGI operative who will protect her at all costs. Even as he falls for this extraordinary woman, the dangerous forces chasing her close in — and Rio vows they' ll never cause Grace such pain again.